Multiplex Real Time PCR Test-System for the Detection of Anthrax Causative Agent - E. A. Tsygankova; E. I. Eremenko; A. G. Ryazanova; O. I. Tsygankova; A. N. Kulichenko (Проблемы особо опасных инфекций, 2013)
Designed is a multiplex PCR-RT test-system for the detection of anthrax causative agent using hybridization fluorescence detection – “ Bacillus anthracis multiplex 3 FRT”. This test-system contains enclosed reference sample for carrying out control procedure in the phase of DNA purification, primers and probes to specific DNA target sequences of the two plasmid and one chromosomal B. anthracis genes. It allows for identification B. anthracis strains both possessing plasmids (one or two) and plasmidless, revealing their genetic pathogenicity potential, and for differentiation between anthrax agent strains and closely related saprophytes belonging to Bacillus species.